Physical preparation for military women of the Naval Force in post-lactation period/Preparación física para mujeres militares de la Fuerza Naval en período de poslactancia - Robert Stalin Alvarado Zedeño; Clemente Fabricio Cevallos Zambrano; Santiago Calero Morales (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Physical-military preparation includes numerous assumptions that regulate the operational readiness of military personnel, establish the basic standards for all active life. Within the work actions to improve or maintain physical condition, the conditions of the military must be taken into account, where the training of the post- lactation period of women must be conditioned to their biological needs. In this sense, the purpose of the research was to implement a training plan to improve the physical condition of military women of the naval force for the post -lactation period. Under an intentional sampling, seven women (31-36 years old) of the Ecuadorian naval force, in the process of breastfeeding, are inserted into a specialized exercise plan to condition them physically. From here, a study is generated in two moments of the preparation of their aerobic endurance, speed and local muscle power. All the assessment tests presented a lower mean performance in the first assessment. From this result, their indicators are exceeded as part of the post -test, Speed Test: 17:56-17:00 (p=0.018), Cooper Test: 16:38-16:12 (p=0.712), Abdominal Test:≈ 36rep-≈ 41rep (p=0.000) and elbow flexion test: 25rep-30rep (p=0.000). During the intervention process, there were no injuries or other difficulties that caused abandonment of the program. The proposed intervention plan improved and conditioned the physical training of military women of the Ecuadorian naval force in a post -lactation state; thus, it significantly improved speed capabilities and local muscle strength, which conditioned aerobic endurance capacity.